Communication Factors for Managing Project with Co-located Team and Virtual Team Affecting Project Success: A Case Study of a Healthcare Facility Service Company in Bangkok - Lertratkosum, Lertvitch; Porananond, Dundusid (Journal for Strategy and Enterprise Competitiveness, 2024)
The objective of this research is to study the communication factors for managing project with co-located team and virtual team affecting Project Success: A Case Study of a Healthcare Facility Service Company in Bangkok. The study was motivated by the significant changes in project management practices due to the COVID-19 crisis. Four communication factors were examined: the Source, message, channel, and receiver, all of which are considered crucial to project success. A quantitative research approach was employed, collecting data from a sample of 63 project participants within the company. The Pearson correlation analysis revealed that all four communication factors had a strong correlation with project success in Virtual Teams, while only the receiver factor showed a strong correlation in Co-located Teams, with the sender, message content, and communication channel factors showing a moderate correlation. These findings underscore the importance of selecting appropriate project management strategies that align with the specific nature of the work and the project environment to enhance efficiency and ensure project success in the future.